Inculcating Anti-Corruption Values in Islamic Educational Institutions - Sontayati Sihite; Muhammad Syukri Albani Nasution; M. Amar Adly (JURNAL AKTA, 2026)
This research examines the regulation of corruption under Islamic law and the implementation of anti-corruption education within educational institutions, focusing on the effectiveness of preventing corruption through the integration of sharia values and positive law. The primary issues addressed are: (1) how corruption is regulated within the framework of Islamic law; (2) how Islamic principles can serve as the basis for anti-corruption education; and (3) how Islamic law can be employed to prevent corruption in schools and universities. The study adopts a normative juridical approach supported by field data collected through interviews. The findings reveal that Islamic law classifies corruption as jināyah ‘alā al-māl al- ‘āmm (a criminal offence against public property), with explicit prohibitions in Qur’an 2:188 and severe warnings against ghulul (embezzlement) and riswah (bribery). However, the implementation of anti-corruption education in schools remains weak: the subject has not been institutionalized as a standalone course, teachers lack the capacity to integrate it into pedagogical strategies, and corruption is often reduced to a mere issue of sin rather than a violation of public trust. At the university level, many lecturers lack specialized competence, resulting in approaches that are largely ceremonial. Such shortcomings contradict the principle of amānah in sharia and undermine the structural objectives of corruption prevention. This study recommends: (1) establishing anti-corruption education as a compulsory subject from early schooling, with measurable behavioral indicators and anti- gratuity protocols; (2) harmonizing Islamic law and positive law within educational regulations and policies; and (3) reorienting the paradigm of corruption from a purely religious issue to a breach of public trust, addressed through an integrated regime of education, ethics, administration, and criminal law. Without these measures, the prohibition of corruption will remain a moral slogan devoid of legal force.